KELANGSUNGAN HIDUP dan PERTUMBUHAN BENIH IKAN LELE DUMBO (Clarias sp) PADA SISTEM RESIRKULASI DENGAN KEPADATAN BERBEDA - Muarif, Muarif (Universitas Djuanda, 2011)
This study was aimed at assessing the effect of stocking density on the survival and growth of Dumbo fish fry raised in a recirculated system. The study was conducted at the the Laboratory of Aquaculture, Department of Aquaculture and Fishery Business and Chemistry Laboratory of the Faculty of Agribusiness and Food Technology, Djuanda University from May to September 2010.A completely randomized design with four treatments and three replications was used. Treatments consisted of stocking density rates of 20, 30, 40, and 50 fish/l. Tanks sized 50x30x30 cm3 were filled in with 25 liter water and fish fry sized 2.24-2.30 cm in the corresponding stocking density rates. Feeding was done ad libitum twice a day at 09.00 and 16.00. Parameters measured included survivability rate, body length growth, daily weight gain, feed efficiency, protein retention, and water quality.Results showed that stocking density gave significant effects (P<0.05) on survivability rate, body length growth, and daily weight gain but not (P>0.05) on feed efficiency and protein retention. The highest survivability rate, body length growth, and daily weight gain of 66.00%; 2.13 cm; and 5.54%, respectively, were obtained in stocking density of 20 fish/l. The quality of water used as a medium of catfish fry raising in each treatment during the experimental period was found to be within good range for the survival and growth of the fry. It was concluded that improving stocking density from 20 to 50 fish/l did not improve Dumbo catfish fry survival and growth rates. Meanwhile, the use of recirculated system was found to maintain medium water quality.